PJMHS 2023
DOI: 10.53350/pjmhs2023171581
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge and Practice Regarding Prevention of Surgical Site Infection at Governmental Hospitals in Wasit City, Iraq 2022

Abstract: Objective: The study was aimed at determining nursing knowledge and practices regarding prevention of surgical site infection in governmental hospitals in Wasit city. Methods: This cross-sectional study was conducted with descriptive design to determine knowledge and practice of nurses who work in surgical wards regarding prevention of SSI in governmental hospitals in Wasit City. A sample of 180 surgical nurses participated in the study (100% response rate); convenience sampling method was used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…It has also been reported that 38.7 to 50.9% of microorganisms isolated from infected surgical wounds exhibit antibiotic resistance patterns. 11 The literature also suggests that the development of competency-based wound infection assessment and management programme for nurses is urgently needed.…”
mentioning
confidence: 99%
“…It has also been reported that 38.7 to 50.9% of microorganisms isolated from infected surgical wounds exhibit antibiotic resistance patterns. 11 The literature also suggests that the development of competency-based wound infection assessment and management programme for nurses is urgently needed.…”
mentioning
confidence: 99%